Within-city dwelling price growth and convergence: trends from Australia's large cities. Issue 1 (2nd January 2021) - Phelps, Christopher; Harris, Mark N.; Ong, Rachel; Rowley, Steven; Wood, Gavin A.
Abstract: Within Australia's larger cities, we observe differences in price dynamics across different sub-periods over the period 2001–2016. A combination of housing market cycles, policy reforms and different new supply configurations offers potential explanations. Neighbourhood dwelling prices within all cities and dwelling types converged during a 2001–2006 sub-period that coincided with strong housing price growth. Shifts in monetary policy as well as tax and housing policy reforms drove this convergence by boosting demand from first homebuyers and investors. Divergence had overtaken convergence in most cities and market segments by the final 2011–2016 sub-period. We argue that falling interest rates were responsible. The findings highlight how price indices based on movements in central measures of the price distribution can offer a poor guide to housing affordability trends at different points in a city's neighbourhood price distribution. They also suggest that monetary policy has differential effects across market segments. These effects are markedly different in periods when monetary policy is relaxed rather than tightened, and have important implications for first homebuyer accessibility and the ability of existing homeowners to trade up.